Basic Fibroblast Growth Factor Fused with Tandem Collagen-Binding Domains from Clostridium histolyticum Collagenase ColG Increases Bone Formation. (25th March 2018) - Sekiguchi, Hiroyuki; Uchida, Kentaro; Matsushita, Osamu; Inoue, Gen; Nishi, Nozomu; Masuda, Ryo; Hamamoto, Nana; Koide, Takaki; Shoji, Shintaro; Takaso, Masashi
Abstract : Basic fibroblast growth factor 2 (bFGF) accelerates bone formation during fracture healing. Because the efficacy of bFGF decreases rapidly following its diffusion from fracture sites, however, repeated dosing is required to ensure a sustained therapeutic effect. We previously developed a fusion protein comprising bFGF, a polycystic kidney disease domain (PKD; s2b), and collagen-binding domain (CBD; s3) sourced from the Clostridium histolyticum class II collagenase, ColH, and reported that the combination of this fusion protein with a collagen-like peptide, poly(Pro-Hyp-Gly)10, induced mesenchymal cell proliferation and callus formation at fracture sites. In addition, C. histolyticum produces class I collagenase (ColG) with tandem CBDs (s3a and s3b) at the C-terminus. We therefore hypothesized that a bFGF fusion protein containing ColG-derived tandem CBDs (s3a and s3b) would show enhanced collagen-binding activity, leading to improved bone formation. Here, we examined the binding affinity of four collagen anchors derived from the two clostridial collagenases to H-Gly-Pro-Arg-Gly-(Pro-Hyp-Gly)12 -NH2, a collagenous peptide, by surface plasmon resonance and found that tandem CBDs (s3a-s3b) have the highest affinity for the collagenous peptide. We also constructed four fusion proteins consisting of bFGF and s3 (bFGF-s3), s2b-s3b (bFGF-s2b-s3), s3b (bFGF-s3b), and s3a-s3b (bFGF-s3a-s3b) and compared their biological activities to those of a previous fusion construct (bFGF-s2b-s3) using a cell proliferation assay in vitro and a mouse femoral fracture model in vivo. Among these CB-bFGFs, bFGF-s3a-s3b showed the highest capacity to induce mesenchymal cell proliferation and callus formation in the mice fracture model. The poly(Pro-Hyp-Gly)10 /bFGF-s3a-s3b construct may therefore have the potential to promote bone formation in clinical settings.